Variasi Waktu Pengasapan Pada Bahan Komposit Serat Sabut Kelapa Terhadap Kekuatan Tarik - Muriman, La Ode Asman; Syarif, Afdal; Ashari, Dedy; Hasfandi, Hasfandi (Teknik Mesin Universitas Halu Oleo, 2023)
Plant fibers used as composite materials have been carried out a lot, but they are not optimal so further research is needed to determine the parameters for making composites. Besides being cheap and easy to find, the use of coconut fiber can also reduce environmental pollution resulting from coconut tree waste. The purpose of this study was to determine the tensile strength of coco fiber composite materials with variations in fumigation. Coco fiber which has previously been smoked will be made into composites which will later be subjected to mechanical test. From the results of the smoked, it was obtained that the water content in the coco fiber decreased by an average of 7% per hour. At 3 hours of smoking time, the water content value was 11.2%, while at 5 hours of smoking time, the water content in the fiber was at 9.7%. The elasticity value for the composite material was 379.1 N/mm2 for the fiber materials which was smoked for 3 hours, this value increased to 532.1 N/mm2 for 4 hours of smoked. There was an increase in the elasticity value of the composite material by 40.3% between the condition of the fiber which was smoked for 3 hours and the fiber which was smoked for 4 hours. Kata kunci: Coco fiber, composite, fumigation, tensile test